IFNAR1 Deficiency Impairs Immunostimulatory Properties of Neutrophils in Tumor-Draining Lymph Nodes - Hussain, Timon; Domnich, Maksim; Bordbari, Sharareh; Pylaeva, Ekaterina; Siakaeva, Elena; Spyra, Ilona; Ozel, Irem; Droege, Freya; Squire, Anthony; Lienenklaus, Stefan; Sutter, Kathrin; Hasenberg, Anja; et al. (Frontiers in Immunology, 2022)
Tumor-draining lymph nodes (TDLNs) are the first organs where the metastatic spread of different types of cancer, including head and neck cancer (HNC), occurs and have therefore high prognostic relevance. Moreover, first anti-cancer immune responses have been shown to be initiated in such LNs via tumor-educated myeloid cells. Among myeloid cells present in TDLNs, neutrophils represent a valuable population and considerably participate in the activation of effector lymphocytes there. Tumor-supportive or tumor-inhibiting activity of neutrophils strongly depends on the surrounding microenvironment. Thus, type I interferon (IFN) availability has been shown to prime anti-tumor activity of these cells. In accordance, mice deficient in type I IFNs show elevated tumor growth and metastatic spread, accompanied by the pro-tumoral neutrophil bias. To reveal the mechanism responsible for this phenomenon, we have studied here the influence of defective type I IFN signaling on the immunoregulatory activity of neutrophils in TDLNs. Live imaging of such LNs was performed using two-photon microscopy in a transplantable murine HNC model. CatchupIVM-red and Ifnar1-/- (type I IFN receptor- deficient) CatchupIVM-red mice were used to visualize neutrophils and to assess their interaction with T-cells in vivo. We have evaluated spatiotemporal patterns of neutrophil/T-cell interactions in LNs in the context of type I interferon receptor (IFNAR1) availability in tumor-free and tumor-bearing animals. Moreover, phenotypic and functional analyses were performed to further characterize the mechanisms regulating neutrophil immunoregulatory capacity. We demonstrated that inactive IFNAR1 leads to elevated accumulation of neutrophils in TDLNs. However, these neutrophils show significantly impaired capacity to interact with and to stimulate T-cells. As a result, a significant reduction of contacts between neutrophils and T lymphocytes is observed, with further impairment of T-cell proliferation and activation. This possibly contributes to the enhanced tumor growth in Ifnar1-/- mice. In agreement with this, IFNAR1-independent activation of downstream IFN signaling using IFN-λ improved the immunostimulatory capacity of neutrophils in TDLNs and contributed to the suppression of tumor growth. Our results suggest that functional type I IFN signaling is essential for neutrophil immunostimulatory capacity and that stimulation of this signaling may provide a therapeutic opportunity in head and neck cancer patients.